Accuracy Assessment for 3-D Target Coordinates Estimation UsingGPS & Total Station - Mahdi, Aala; Tawfiq, Nabeel; Hussein, Ali (Iraqi Journal of Science, 2024)
The Target coordinates estimation in the real world (3-D) was importantapplications in the geodesy and many remote sensing applications, for this purpose,the GPS/DGPS, and the Total Station were used to create and estimate the newtarget coordinate. In this paper, the Total Station Leica 1200 with Garmin navigatorGPS were used to extract the 3-D coordinates of target from the measurement of TSposition. For six point for one station. The Garmine GPS navigator was use to findthe coordinates for each points and the total station position. Many mathematicalprocess were used to evaluate the results of accuracy using written subroutines inMatlab (version 7.4.0 R 2007a) environmental.